PA/MR imaging-guided precision phototherapy and efficacy evaluation of hepatocellular carcinoma utilizing a targeted multifunctional nanoprobe - Qi, Shuo; Zhou, Lei; Liu, Weinan; Shen, Lian; Yao, Yuping; Tian, Bingzhang; Liu, Changjun; Cheng, Wei; Chen, Kang (Frontiers in Immunology, 2025)
IntroductionEarly-stage hepatocellular carcinoma (HCC) poses a significant challenge due to its poor prognosis, necessitating advancements in diagnostic and therapeutic strategies. The integration of near-infrared photoacoustic (PA) imaging with magnetic resonance (MR) imaging offers enhanced temporal and spatial resolution, exceptional optical contrast, and profound tissue penetration, positioning this combination as a highly promising technique for accurate and sensitive HCC diagnosis.MethodsIn this study, we developed a multifunctional and highly biocompatible nanoplatform, designated as ICG/Mn-PDA-PEG-CXCR4 (IMPP-c). This nanoplatform is designed to diagnose and treat early-stage HCC through PA/MR imaging-guided noninvasive photothermal therapy (PTT) and photodynamic therapy (PDT).ResultsBoth in vitro and in vivo experiments demonstrated enhanced accumulation of IMPP-c nanoparticles (NPs) within HCC. Notably, the dual-modal PA/MR imaging facilitated by IMPP-c achieved high resolution and substantial deep tissue penetration, enabling precise localization of early orthotopic small hepatocellular carcinoma (SHCC) lesions. In vivo tumor phototherapy experiments, guided by PA/MR imaging, revealed that SHCC was completely eradicated through noninvasive PTT/PDT without recurrence. Additionally, the metabolism of IMPP-c NPs was observed in major organs throughout the treatment process, confirming its reliable biocompatibility.DiscussionThis study introduces a novel method for diagnosing and implementing non-invasive therapeutic interventions in early HCC using nanoparticle systems such as IMPP-c, paving the way for potential future clinical applications.